1997
DOI: 10.1152/ajpendo.1997.273.6.e1065
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thyroid status on hepatic α1-adrenoreceptor responsiveness

Abstract: The present work aimed to elucidate the influence of thyroid functional status on the α1-adrenoreceptor-induced activation of hepatic metabolic functions. The experiments were performed in either a nonrecirculating liver perfusion system featuring continuous monitoring of portal pressure,[Formula: see text], pCa, and pH, or isolated hepatocytes from euthyroid, hyperthyroid, and hypothyroid rats. Hypothyroidism decreased the α1-adrenergic stimulation of respiration, glycogen breakdown, and gluconeogenesis. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…Our observations are consistent with previous reports regarding enhanced intracellular cAMP content in different cells after THs application (Yen 2001, Shih et al 2004. THs modulated the activity of phosphodiesterase (Morgan et al 1982) and mimicked the effects of cAMP-inducing hormones (Muller & Seitz 1983, Daza et al 1997. Furthermore, cAMPinduced PKA activation has been shown to mediate THs effects (Lin et al 1999), such as potentiation of growth hormone receptor signaling in cancer cells (Shih et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations are consistent with previous reports regarding enhanced intracellular cAMP content in different cells after THs application (Yen 2001, Shih et al 2004. THs modulated the activity of phosphodiesterase (Morgan et al 1982) and mimicked the effects of cAMP-inducing hormones (Muller & Seitz 1983, Daza et al 1997. Furthermore, cAMPinduced PKA activation has been shown to mediate THs effects (Lin et al 1999), such as potentiation of growth hormone receptor signaling in cancer cells (Shih et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The status of THs modulated the steady-state levels of specific G-proteins induced by b-adrenergic agonists (Daza et al 1997). It has also been shown that THs positively regulated epidermal growth factor receptor signaling pathway (Lin et al 1999, Di Fulvio et al 2000, Shih et al 2004) -established survival regulator of Fas-induced apoptosis (Gibson et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Epinephrine (50 nmol/L)-stimulated glucose release during control experiments (28.3 Ϯ 2.8 µmol/g liver within 30 minutes) was similar to that of 1,000 nmol/L phenylephrine in hepatocytes from fed rats (ϳ27 µmol/g liver within 30 minutes) 34 and even higher than in other liver perfusion systems (ϳ16 µmol/g liver within 30 minutes). 35 Insulin and leptin reduced, but did not completely block, epinephrinestimulated glycogenolysis. 36,37 However, simultaneous infusion of insulin and leptin did not additively inhibit epinephrine-induced hepatic glycogenolysis (Fig.…”
Section: Studies Of Postprandial Glycogenolysismentioning
confidence: 97%
“…In some organs like the heart, thyroid hormones increase beta-adrenergic receptors, 2 while in the liver and smooth muscle cells of vessel walls, alpha-adrenergic receptors are increased by thyroid hormones. 1,7 It is probable that thyroid hormones increase cholinergic, histaminic and gastrin receptors in chief cells and parietal cells of stomach. Kayode et al have observed that thyroxin increases mitotic activity of crypt cells of digestive tract in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones affect the function of some body organs including cardiovascular [1][2][3] and nervous systems, [4][5][6] liver, 7 development and reproductive systems and growth process. [8][9] There is evidence that they also affect gastric acid and pepsin secretions.…”
mentioning
confidence: 99%